The lived experiences of wives of first time myocardial infarction survivors during the convalescent period - McLeod, Wendy (Division of Nursing and Midwifery, 2017)
There is evidence that wives of first time myocardial infarction survivors play a crucial role during the convalescent period. A knowledge deficit exists however, regarding the significance of their experiences during this time. The aim of this study therefore, was to investigate and illuminate the lived experiences of wives of first time myocardial infarction survivors during the first six to eight weeks of their husbands' convalescent period. The inquiry paradigm chosen for this study was the qualitative approach and the research strategy used was hermeneutic phenomenology. Max van Manen's six procedural research activities guided the methodological processes of this study. A pilot interview was conducted using the Free Attitude Interview Technique, following which four study interviews were done with participants who met the inclusion criteria. Qualitative analysis revealed eight central themes that described the lived experiences of the participants. They were: 1) being a protective shield; 2) life changes; 3) facets of the relationship change; 4) meeting additional role responsibilities; 5) living with fear; 6) drawing from the support fund; 7) causal explanations for the myocardial infarction and 8) the need for knowledge. The study findings are discussed in relation to the available literature and recommendations are made for nursing research, practice and education. The knowledge gained from this study will enable nurses to plan and implement nursing interventions that will better prepare, support and equip wives during the convalescent period. This in turn will assist the wives to enhance family resources and promote their husbands' readjustment during the convalescent period.